Peran Pengawas Ketenagakerjaan dalam Pemenuhan Hak Pekerja yang Mengalami Pemutusan Hubungan Kerja (PHK) - Rusyaman, Jasmine Gitarahmi; Karsona, Agus Mulya; Singadimedja, Holyness N (Universitas Muhammadiyah Ponorogo, 2025)
Labor inspectors serve the function of overseeing and ensuring the enforcement of labor regulations, including guaranteeing the fulfillment of workers' rights in cases of termination of employment. As a consequence of termination practices, workers are entitled of severance pay, rewards for length of service, and reimbursement of other entitlements in accordance with applicable regulations. This study focuses on the legal protection and the impact of labor inspectors’ performance on the fulfillment of workers' rights in termination cases. The approach employed in this study is a normative juridical method. The findings indicate that the active role of labor inspectors in fulfilling workers’ rights following termination can be carried out upon receiving a complaint from the affected worker or based on a directive from their superior. This is closely related to the limited authority of labor inspectors. Furthermore, the high number of labor law violations and the imbalance between the number of labor inspectors and the number of existing companies indicate that labor inspection implementation has not yet been optimal.